2011
DOI: 10.1175/2010mwr3247.1
|View full text |Cite
|
Sign up to set email alerts
|

Finescale Doppler Radar Observation of a Tornado and Low-Level Misocyclones within a Winter Storm in the Japan Sea Coastal Region

Abstract: Life histories of low-level misocyclones, one of which corresponded to a tornado vortex within a winter storm in the Japan Sea coastal region on 1 December 2007, were observed from close range by X-band Doppler radar of the East Japan Railway Company. Continuous plan position indicator (PPI) observations at 30-s intervals at the low-elevation angle revealed at least four cyclonic misocyclones within the head of the comma-shaped echo of the vortical disturbance under winter monsoon conditions. The meso-b-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 43 publications
6
33
3
Order By: Relevance
“…The intensification of the misocyclone after landfall is apparently in contrast to previous reports of winter tornadic vortices and misocyclones developing over the Japan Sea and dissipating after landfall (Kobayashi et al 2007;Inoue et al 2011;Kato et al 2015). According to the present results, the evolution of the misocyclone is probably related to the parent cloud's development.…”
Section: Summary and Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The intensification of the misocyclone after landfall is apparently in contrast to previous reports of winter tornadic vortices and misocyclones developing over the Japan Sea and dissipating after landfall (Kobayashi et al 2007;Inoue et al 2011;Kato et al 2015). According to the present results, the evolution of the misocyclone is probably related to the parent cloud's development.…”
Section: Summary and Discussioncontrasting
confidence: 96%
“…Many winter misoscale vortices including winter tornadoes (hereafter called winter misocyclones) are generated and developed over the Sea, and travel with the monsoon to the coast. Such winter misocyclones have been found in various mesoscale cloud systems including a convective cloud developed in part of a cloud band (Kobayashi et al 2007), a band-shaped cloud at the leading edge of a frontal zone (Inoue et al 2011), and a locally developed snow cloud band (Kato et al 2015). These previous studies reported changes in the structure of those vortices after landfall such as the dissipation of the vortices on land possibly caused by the effect of ground surface friction on the angular momentum of the vortices.…”
Section: Introductionmentioning
confidence: 88%
“…Inoue et al (2011) successfully detected vortices such as tornados and mesocyclones, although not dust devils, during a winter storm event with the use of a low-level scanning X-band Doppler radar. Fujiwara et al (2011Fujiwara et al ( , 2012) used a three-dimensional scanning Doppler lidar to detect dust-devil-like vortices that develop in the daytime under fair-weather convective conditions over an urban area.…”
Section: Japanmentioning
confidence: 99%
“…Representative disturbances accompanied by a wind shear and a tornado are a synoptic-scale cold front (e.g., Okazaki 2009) and the Japan-Sea Polar-Airmass Convergence Zone (JPCZ) (e.g., Kobayashi 2002) that extends from the base of the Korean Peninsula to the Hokuriku district. Mesoscale shear lines in snowbands also occasionally cause meso-γ-scale vortices (Kawashima and Fujiyoshi 2005) and micro-scale vortices including a tornado (Mashiko et al 2009;Inoue et al 2011). In recent decades, many studies have been conducted to reveal the detailed structure and growth mechanisms of micro-to meso-β-scale vortices from Doppler radar data and through numerical simulation (e.g., Kawashima and Fujiyoshi 2005;Kobayashi et al 2007;Mashiko et al 2009;Inoue et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale shear lines in snowbands also occasionally cause meso-γ-scale vortices (Kawashima and Fujiyoshi 2005) and micro-scale vortices including a tornado (Mashiko et al 2009;Inoue et al 2011). In recent decades, many studies have been conducted to reveal the detailed structure and growth mechanisms of micro-to meso-β-scale vortices from Doppler radar data and through numerical simulation (e.g., Kawashima and Fujiyoshi 2005;Kobayashi et al 2007;Mashiko et al 2009;Inoue et al 2011). However, the structure of the shear lines, which cause such vortical disturbances and/or wind gusts, are still poorly understood except for the JPCZ (e.g., Nagata et al 1986;Nagata 1991).…”
Section: Introductionmentioning
confidence: 99%